The usefulness of peri-trigger female reproductive hormones (delta-FRH) in predicting oocyte maturation in normal ovarian reserve patients who received in vitro fertilization-embryo transfer: a retrospective study - He, Lina; Xu, Qing; Wan, Fuming; Hao, Li; Qiu, Yamin; Ran, Xu; Lin, Jie; Chen, Wei (PeerJ, 2024)
Objectives To evaluate the efficacy of peri-trigger female reproductive hormones (FRHs) in the prediction of oocyte maturation in normal ovarian reserve patients during the in vitro fertilization-embryo transfer (IVF-ET) procedure. Materials and Methods A hospital database was used to extract data on IVF-ET cases from January 2020 to September 2021. The levels of female reproductive hormones, including estradiol (E2), luteinizing hormone (LH), progesterone (P), and follicle-stimulating hormone (FSH), were initially evaluated at baseline, the day of the trigger, the day after the trigger, and the day of oocyte retrieval. The relative change in E2, LH, P, FSH between time point 1 (the day of trigger and baseline) and time point 2 (the day after the trigger and day on the trigger) was defined as E2_RoV1/2, LH_RoV1/2, P_RoV1/2, and FSH_RoV1/2, respectively. Univariable and multivariable regression were performed to screen the peri-trigger FRHs for the prediction of oocyte maturation. Results A total of 118 patients were enrolled in our study. Univariable analysis revealed significant associations between E2_RoV1 and the rate of MII oocytes in the GnRH-agonist protocol group (p < 0.05), but not in the GnRH-antagonist protocol group. Conversely, P_RoV2 emerged as a potential predictor for the rate of MII oocytes in both protocol groups (p < 0.05). Multivariable analysis confirmed the significance of P_RoV2 in predicting oocyte maturation rate in both groups (p < 0.05), while the association of E2_RoV1 was not significant in either group. However, within the subgroup of high P_RoV2 in the GnRH-agonist protocol group, association was not observed to be significant. The C-index was 0.83 (95% CI [0.73–0.92]) for the GnRH-agonist protocol group and 0.77 (95% CI [0.63–0.90]) for the GnRH-antagonist protocol group. The ROC curve analysis further supported the satisfactory performance of the models, with area under the curve (AUC) values of 0.79 for the GnRH-agonist protocol group and 0.81 for the GnRH-antagonist protocol group. Conclusions P_RoV2 showed significant predictive value for oocyte maturation in both GnRH-agonist and GnRH-antagonist protocol groups, which enhances the understanding of evaluating oocyte maturation and inform individualized treatment protocols in controlled ovarian hyperstimulation during IVF-ET for normal ovarian reserve patients.
Keywords: Oocyte maturity; Female reproductive hormone; In vitro fertilization-embryo transfer; Biomarker; Peri-trigger management